2016
DOI: 10.1021/acs.jpcb.5b09668
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrotropic Action of Hydrotrope Sodium Cumene Sulfonate on the Solubility of Di-t-Butyl-Methane: A Molecular Dynamics Simulation Study

Abstract: Hydrotropes are special class of amphiphilic molecules that have an ability to solubilize the insoluble or sparingly soluble molecules in water. To find out the mechanism of hydrotropic action of hydrotropes on hydrophobic molecules, we have carried out classical molecular dynamics simulation of hydrophobic solute di-t-butyl-methane (DTBM) and hydrotrope sodium cumene sulfonate (SCS) in water with a regime of SCS concentrations. Our study demonstrates that, above the minimum hydrotrope concentration (MHC), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 68 publications
8
45
2
Order By: Relevance
“…Most hydrotropes aggregate above MHC ( 18 , 19 ), or critical aggregate concentration, to solubilize hydrophobic materials. We determined the MHC of p -TsOH from the conductivities of its solutions ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most hydrotropes aggregate above MHC ( 18 , 19 ), or critical aggregate concentration, to solubilize hydrophobic materials. We determined the MHC of p -TsOH from the conductivities of its solutions ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of variations in hydrotrope structures, the exact mechanism of a given hydrotrope solubilizing compounds is still under debate ( 18 ). However, most researchers believe that most hydrotropes aggregate above the MHC ( 18 , 19 ). Aggregation is pronounced in the presence of a hydrophobic solute ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrotropic phenomenon was discovered in 1916 by Neuberg [52] . It refers to solubilization of hydrophobic materials in aqueous systems by hydrotrope aggregation around the solute [53–55] . Current applications are mainly in the pharmaceutical industry [56] .…”
Section: Mechanism Of Acid Hydrotropic Fractionation Of Lignocellulosesmentioning
confidence: 99%
“…They can self-aggregate in aqueous solution above minimum hydrotrope concentration (MHC) [ 37 ]. Most interestingly hydrotropes have an ability to solubilize the insoluble or sparingly soluble molecules in water [ 38 , 39 ]. In our previous study we have shown the mechanism of hydrotropic action by formulating griseofulvin with hydrotrope sodium cumene sulfonate (SCS) molecules (See Fig 1 (c) ) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%